2021
DOI: 10.33003/fjs-2021-0501-507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Sex on Morphometric Measurements of Sahelian Goats in Faskari Local Government Area of Katsina State

Abstract: This research was conducted to determine the effect of age and sex on morphometric measurements and estimate correlation between body weights and morphological traits of Sahelian goat in Faskari Local Government Area, Katsina state. Experimental animals aged from 1-5 years were used for this study and were identified using physical appraisal. Physically healthy of both sexes and non-pregnant goats were sampled.  The pairs of permanent incisors in the dentition of the goat were used to determine age, body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The results revealed a significant effect of sex, age and agro ecological zones (P < 0.01) on body weight, and various measurements of body. Our results in the current study are also similar to previous studies (Muner et al, 2018, Aliyu et al, 2021. The results of previous studies indicated that phenotypic characterization i.e., body weight and linear body measurements could be useful in devising efficient input system, breed preservation and conservation and might also be useful in devising enhancement strategies for exploiting genetic resources (Tsegaye et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed a significant effect of sex, age and agro ecological zones (P < 0.01) on body weight, and various measurements of body. Our results in the current study are also similar to previous studies (Muner et al, 2018, Aliyu et al, 2021. The results of previous studies indicated that phenotypic characterization i.e., body weight and linear body measurements could be useful in devising efficient input system, breed preservation and conservation and might also be useful in devising enhancement strategies for exploiting genetic resources (Tsegaye et al, 2013).…”
Section: Discussionsupporting
confidence: 91%